RME-based Absolute Value Worksheet Design as an Effort to Improve Mathematical Thinking Ability of Tribhuwana Tunggadewi University Students - Elita Mega Selvia Wijaya; Rudy Setiawan (MEJ (Mathematics Education Journal), 2021)
The aim of this study was to produce a mathematics worksheet on absolute value material based on the Realistic Mathematical Education (RME) approach. The location of this research is Tribhuwana Tunggadewi University. The development model in this research is designed based on ADDIE, which includes: (A) analysis, which is about curriculum analysis and needs analysis; (D) design, containing the preparation of the worksheet; (D) development, intended in the process of developing an RME-based absolute value worksheet; (I) implementation, namely product testing conducted for small groups and for large groups with the aim of obtaining practical data and data on mathematical thinking skills; (E) evaluation, which is carried out in data analysis refers to the implementation stage. The results of product validation through a google form questionnaire conducted by media experts were 92%, material experts 87%, small group test 91%, large group test 88%, and students' mathematical thinking ability test results reached 83%. Based on these data, it shows that the designed worksheet is feasible and practical in improving the mathematical thinking skills of Tribhuwana Tunggadewi University students.